ФОРМУВАННЯ ІНТЕЛЕКТУАЛЬНОЇ КУЛЬТУРИ УЧНІВ - О. А. Пермяков; Н. І. Зеленкова; Л. В. Бурман (Academy of Cognitive and Natural Sciences, 2012)
У статті витлумачено основні поняття досліджуваної проблеми, проаналізовано зміст інтелектуальної культури учнів, окреслено основні шляхи її формування. Ключові слова: учні, інтелект, культура, інтелектуальна культура.     In the article interpretation of the basic concept of the subject, analyzed the students intellectual culture, illustrates the key ways of its formation.   Key words: students, intellect, culture, intellectual culture.